2016
DOI: 10.1002/da.22503
|View full text |Cite
|
Sign up to set email alerts
|

A STUDY OF THE PATTERN OF RESPONSE TO rTMS TREATMENT IN DEPRESSION

Abstract: A meaningful percentage (>40%) of patients respond to a course of rTMS treatment. Response does vary with a number of clinical and demographic variables but none of these variables exert a sufficiently strong influence on response rates to warrant using these criteria to exclude patients from treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
103
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 28 publications
9
103
4
2
Order By: Relevance
“…BD, bipolar depressive; ERD, French Retardation Rating Scale for Depression; HC, healthy controls; MADRS, Montgomery–Åsberg Depression Rating Scale; MoCA, Montreal Cognitive Assessment; rTMS, repetitive transcranial magnetic stimulation; UD, unipolar depressive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BD, bipolar depressive; ERD, French Retardation Rating Scale for Depression; HC, healthy controls; MADRS, Montgomery–Åsberg Depression Rating Scale; MoCA, Montreal Cognitive Assessment; rTMS, repetitive transcranial magnetic stimulation; UD, unipolar depressive.…”
Section: Resultsmentioning
confidence: 99%
“…In a more explanatory way, our second purpose examined whether an rTMS treatment could concomitantly improve PMR and VF capacities, as a relevant marker characteristic of the cognitive component of PMR. Accordingly, Serafini et al validated the role of rTMS as a valuable and promising treatment for enhancing some neurocognitive features like VF capacities …”
mentioning
confidence: 99%
“…Results from six RCTs showed that as a whole, 68/146 (46.6%) and 15/84 (22.1%) subjects in the active or sham rTMS groups were classified as responders, respectively. Also, in meta-analysis by Fitzgerald et al (2016) which studied the rate of clinical response and remission, and the demographic and clinical predictors of response to rTMS from 11 clinical trials, remission rate was 31%, and the rate of clinical response was 46%. The results from our study showed that in a group of patients treated with rTMS in combination with medication 21/41 (51.2%) were responders (a decrease in HAM-D scores of at least 50%) and 21/41 (51.2%) remitters (scores in HAM-D of 7 or less).…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive transcranial magnetic stimulation (rTMS) is now an established treatment for patients with major depressive disorder (MDD) who have failed to respond to one or more medication trials supported by multiple trials and meta‐analysis . Response rates seen in groups of patients with treatment‐resistant symptoms have been reported between 30% and 50%, although remission rates are lower than this . However, like all antidepressant strategies, it is recognized that patients may relapse in the 6–12 months following rTMS treatment .…”
Section: Maintenance Strategies After a Successful Course Of Rtmsmentioning
confidence: 99%
“…1 Response rates seen in groups of patients with treatment-resistant symptoms have been reported between 30% and 50%, although remission rates are lower than this. 2 However, like all antidepressant strategies, it is recognized that patients may relapse in the 6-12 months following rTMS treatment. 3 For this reason, there has been growing interest in the potential use of rTMS as a maintenance therapeutic strategy.…”
Section: Is Maintenance Repetitive Transcranial Magnetic Stimulation mentioning
confidence: 99%